Defining CYP3A4 structural responses to substrate binding. Raman spectroscopic studies of a nanodisc-incorporated mammalian Cytochrome P450 - Mak, Piotr J. (2011)
Resonance Raman (RR) spectroscopy is used to help define active site structural responses of nanodisc-incorporated CYP3A4 to the binding of three substrates; bromocriptine (BC), erythromycin (ERY) and testosterone (TST). We demonstrate that nanodisc-incorporated assemblies reveal much more well-defined active site RR spectroscopic responses compared to those normally obtained with the conventional, detergent-stabilized, sampling strategies. While, ERY and BC are known to bind to CYP3A4 with a 1:1 stoichiometry, only the BC induces a substantial conversion from low- to high-spin state, as clearly manifested in the RR spectra acquired herein. The third substrate, TST, displays significant homotropic interactions within CYP3A4, the active site binding up to 3 molecules of this substrate, with the functional properties varying in response to binding of individual substrate molecules. While such behavior seemingly suggests the possibility that each substrate binding event induces functionally important heme structural changes, up to this time spectroscopic evidence for such structural changes has not been available. The current RR spectroscopic studies show clearly that accommodation of different size substrates, and different loading of TST, do not significantly affect the structure of the substrate-bound ferric heme. However, it is here demonstrated that the nature and number of bound substrates do have an extraordinary influence on the conformation of bound exogenous ligands, such as CO or dioxygen and its reduced forms, implying an effective mechanism whereby substrate structure can impact reactivity of intermediates so as to influence function, as reflected in the diverse reactivity of this drug metabolizing cytochrome.